Genetics of epilepsy - Sisodiya, Sanjay (Henry Stewart Talks, 2014)
Epilepsy and genetics, Significant contribution of genetics to many epilepsies, Many types of variation, and methods to detect them, Importance of correct interpretation, Will likely revolutionise understanding